The music of the Netherland Antilles why eleven Antilleans knelt before Chopin's heart - Brokken, Jan 1949- (Caribbean Studies Series, 2015)
Why Eleven Antilleans Knelt Before Chopin's Heart is not your usual music handbook. The book’s curious title refers to the presence of eleven Antilleans at the service held in the Warsaw church to commemorate the 150th anniversary of Fryderyk Chopin’s death in October 1999 where the composer’s heart is kept in an urn, whilst the rest of his mortal remains lie in Paris. The item which Brokken had read in a German newspaper triggered him to start writing the book based on notes he had been taking while living on Curacao from 1993 to 2002. Anyone interested in discovering an overlooked chapter of Caribbean music and music history will be amply rewarded with a Dutch Caribbean perspective on the pan- Caribbean process of Creolization and the history and legacy of slavery in shaping culture and music in the New World. Brokken’s portraits of prominent Dutch Antillean composers, are interspersed with anecdotes, and forays into cultural and music history. Brokken puts the Dutch Caribbean’s contributions into a broader context by also examining the 19th century phenomenon, pianist Louis Moreau Gottschalk from New Orleans and Manuel Samuel from Martinique. Brokken explores the African component of Dutch Antillean music – examining the history of the rhythm and music known as tambú as well as American jazz pianist Chick Corea's fascination with the tumba rhythm from Curacao. The book ends with a discussion of how recent Dutch Caribbean adaptations of European dance forms has shifted from a classical musical approach to contemporary forms of Latin jazz